DIFFERENTIAL DIAGNOSIS OF PSORIASIS - P. Lisi (PAGEPress Publications, 2011)
The clinical diagnosis of psoriasis is relatively easy, especially when the lesions consist of erythematous, silvery white scaly, sharply demarcated, indurated plaques, distributed symmetrically on the extensor surfaces of limbs, the lower back and the scalp. These clinical features reflect the histopathological findings observed in active lesions, characterized by parakeratosis, acanthosis of the epidermal ridges, tortuous and dilated blood vessels, and perivascular leukocytic infiltrate; the Munro microabscess and the spongiform pustule of Kogoj are diagnostic. Diagnostic doubts, however, may arise in several clinical variants and atypical cases (guttate psoriasis, follicular or spinulosic psoriasis, erythrodermic psoriasis, pustular psoriasis) or when the psoriatic lesions are localized in particular sites (palms, soles, scalp, body folds, penis, nails). The value of erythemato-papulosquamous psoriasiform eruptions occurring during or after the administration of a diagnostic or therapeutic agent especially in psoriatic subjects is discussed. Key words: Psoriasis, differential diagnosis, skin diseases, clinical features, histopathological aspects